Closing the Credit Gap for Formal and Informal Micro, Small, and Medium Enterprises - Stein, Peer; Ardic, Oya Pinar; Hommes, Martin (International Finance Corporation, Washington, DC, 2015)
Job creation and economic growth through private sector development have become primary areas of focus for policy makers around the world in the aftermath of the global financial crisis. Recent evidence points to the importance of small and medium enterprises (SMEs) in providing employment across countries. In addition to employing the largest number of people in aggregate, SMEs generate the most new jobs. But SMEs also face many challenges in day-to-day operations and to grow. This note is a report back on the state of the credit gap for MSMEs with this new and updated data, while providing additional focus on the sizable informal enterprise sector in the developing world. In addition, this report examines various operational challenges that small and informal firms face, and some formalization obstacles they often cite as the primary reasons for not registering their business. A framework to differentiate the informal sector is offered, with the intention of segmenting the vast landscape of informal firms some of which exist today due to opportunistic behavior, while others are just trying to survive and to better design specific interventions depending on the stage of development and the willingness of the firm to register its business. The rest of this report is organized as follows. Section I focuses on the credit gap for formal MSMEs, and offers some innovative models and interventions that can be used to more fully meet the financial and non-financial needs of formal MSMEs. Section II focuses exclusively on informal enterprises, and goes beyond the access to finance paradigm, describing the operational challenges faced by informal firms, reviewing the experiments that have tried to induce higher rates of formalization, and looking at a series of private sector models that if combined, could more fully meet the needs of informal firms.